MANAJEMEN PEMBELAJARAN BAHASA ASING PADA SMK BERBASIS PONDOK PESANTREN - Diana, Riska; Suyatno, Suyatno; Sudarsono, Bambang (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
This study aims to analyze the management of foreign language learning at SMK Darul Amanah, a school based in a pesantren (Islamic boarding school), which integrates the learning of Arabic and English into students' daily lives. Foreign language learning at this school is designed to develop students' language skills in both religious and professional contexts. This research employs a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation. The findings reveal that the planning of foreign language learning at SMK Darul Amanah involves clear objectives, focusing on mastering Arabic for religious purposes and English for professional needs. The implementation of learning is carried out intensively through various extracurricular programs such as Muhadloroh, Mufrodat Pagi, and Muhadasah Yaumiyah, which enable students to practice speaking in both languages. Evaluation is conducted through written tests, oral assessments, and portfolios. This contextual and practice-based learning approach has proven effective in improving students' foreign language skills, with the integration of language use into daily life further enhancing natural language acquisition. This research contributes to the development of foreign language learning based on pesantren models in Indonesia.